On Repeated Games with Imperfect Public Monitoring: Characterization of Continuation Payoff Processes - Mathias Staudigl (Bielefeld University, Center for Mathematical Economics (IMW), 2014)
This note contains complementary information to the paper Staudigl and Steg (2014). We present a martingale characterization of continuation payoff processes in a class of repeated games with imperfect public monitoring. Our martingale approach allows us to work out a clear connection between the discrete time and continuous time payoff processes. A general proof of convergence is the open issue in this literature, and I strongly belief that the characterization result reported here is the key to solve this problem.
Keywords: 330; repeated games; public perfect equilibrium; martingale representation